Studi Peningkatan Usia Guna Waduk Songputri Akibat Dampak Sedimentasi - Emiliawati, Sris Novita; Sholichin, Moh; Haribowo, Riyanto (Jurnal Teknologi dan Rekayasa Sumber Daya Air, 2022)
Songputri Reservoir located in Wonogiri Regency which was built in 1977-1984 needs to be handled such as vegetation, checkdam construction, and dredging to find out how much additional the reservoir's useful life, besides that it is also necessary to calculate the erosion and sedimentation in the Songputri watershed. The data needed is monthly rainfall data, number of rainy days, and maximum daily data used to calculate the value of erosivity (R), a soil type map to determine the erodibility value (K), a slope map to determine the LS factor, and a land use map to determine the CP value. The calculations will using USLE method assisted by the ArcMap 10.4 application. From the results, it is known that the erosion is 23,157.57 tons/year, the sedimentation is 1,976.71 tons/year, and the reservoir useful life is 22 years. After that, reforestation is carried out on an area of 14.28 ha, construction of 6 checkdams, and dredging in the Songputri Reservoir. After that, the erosion and sedimentation were calculated using the same formula, it is known that the erosion is 7,735.39 tons/year, the sedimentation is 660.29 tons/year, and the useful life of the reservoir is increased to 67 years